Improving the international competitiveness of universities in the global digital space - V. V. Bondarenko; K. S. Taisheva; T. V. Tampey; D. P. Penzina (Вестник университета)
The article examines the competitiveness concept of universities, presented by modern researchers. The most important factors of increasing the international competitiveness of universities in the global digital space are identified and analyzed. The internationalization importance of teaching personnel and student staff, as well as the introduction of international practices using digital technologies into the universities educational programs’ is established. The results of a sociological survey of students in Russian higher educational institutions are presented. The factors that have the greatest influence on the choice of university and educational program by students are determined. The attitude of students to gaining international learning experience in the digital educational space has been studied and practice-oriented recommendations for improving the international competitiveness of universities have been prepared. In addition, foreign policy factors influencing the intensity of international activity of Russian higher education institutions were taken into account when making recommendations.